The independent director on the board of company directors - McCabe, Margaret (Graduate School of Business, Curtin University of Technology, 2006)
This paper examines the views of directors of public listed Australian companies regarding the role of the independent director and the significance of that role in relationship to the composition of the Board of Company Directors (BOCD). The preferred model for board composition in Australian public listed companies is that of a majority of Non-Executive Directors. Whilst this model is promoted in Australia there is conflicting evidence surrounding the claim that a majority of independent members in the board structure contributes to high levels of performance.The data reported were collected in qualitative research which examined the perceptions of governance practice held by a group of Australian company directors holding positions on boards of public listed companies between 1997 and 2000. The research is looking at directors? perceptions of how and why independent directors contribute to board performance The analysis indicates that participating directors were convinced that a majority of Non-Executive Directors provided a safeguard for a balance of power in the board/management relationship. The difference between Non-Executive Directors, who are also independent directors, and Non-Executive Directors who are not independent, was an important distinction which was highlighted. The capacity for board members to think independently was seen to be enhanced, but not necessarily ensured, with majority membership of Non-Executive Directors. However, a majority of independent minds expressing multiple points of view was perceived to reduce the board room hazard of ?group think?.